SCOZ: A system‐wide causal profiler for multicore systems. (5th November 2020) - Ahn, Minwoo; Kim, Donghyun; Nam, Taekeun; Jeong, Jinkyu
Abstract: The increased complexity of hardware and software makes it difficult to analyze programs with conventional profilers. The causal profiling technique is introduced to solve the problem of conventional profilers. The causal profiling technique finds the bottleneck of the program and shows the effect of optimizing it. COZ, the newest causal profiler, exploits a technique called virtual speedup to perform causal profiling without actually optimizing program codes. However, it can only profile multithreaded applications, and cannot profile multiprogram applications and operating system (OS) kernel codes, thereby limiting the use of causal profiling. This article introduces SCOZ, a system‐wide causal profiler that addresses these limitations. The proposed profiler changes the target of virtual speedup from threads to CPU cores, thereby expanding the profiling coverage to diverse applications as well as OS kernel codes. To verify our profiler, we profiled multithreaded and OS kernel‐intensive applications. For multithread applications, our profiler shows identical results to what COZ provides. For the OS kernel‐intensive applications, our profiler identifies identical bottlenecks that previous OS scalability studies have pinpointed. Finally, we verified the profiling capability of the proposed profiler by profiling and optimizing multiprocess applications in the NAS parallel benchmark suite.